Smart failure insensitive routing: smart failure insensitive routing to enhance resource utilisation and robustness. Issue 2 (1st June 2013) - Kamrul, Islam Mohammad; Ouédraogo, Ihsen Aziz; Oki, Eiji
Abstract : As the Internet takes an increasingly central role in the authors communications infrastructure, the slowness of routing convergence after network failure is becoming a significant problem in the current link‐state‐based routing protocol. There is an alternative approach, which is to compute backup routes that allow the failure to be repaired locally by the routers that detect the failure without informing other routers of the failure immediately. Failure insensitive routing (FIR) adopts this approach, in which packet forwarding is based on not only the destination but also the link it arrives from. However, FIR faces two problems. First, a packet may travel an unnecessary path, which degrades resource utilisation efficiency. Second, FIR may fail to set a re‐route path even though an active path is available. This study proposes a resilient routing scheme that avoids these two problems by enhancing FIR. It is named smart FIR (S‐FIR). Upon failure, S‐FIR employs a backup routing table based on the unexpected link from which a packet arrives so that subsequent packets can be forwarded to a different next hop to avoid roll back, whereas the original FIR forwards every packet based on the current working routing table. Numerical results indicate that S‐FIR reduces the path length significantly, compared with the original FIR. In addition, in case of any link failure, S‐FIR is proven to guarantee that any packet reaches its destination as long as there is a valid path. S‐FIR provides more robust routing than FIR.